An artificial olfactory system and an application thereof - Hamidon, Mohd Nizar; Lotfivandvahed, Nasser (2013)
The present invention relates to an artificial olfactory system (100), comprising of an inlet (101); a gas chamber (110) having a detector means, connected to a data acquisition system (104); a heater (112) and a plurality of fans (115); a humidity absorber (111); an outlet (102); a vacuum pump (103); characterized by the detector means having a plurality of sensors (121) in each of a plurality of clusters (120), wherein the plurality of sensors (121) in each of the plurality of clusters (120) comprises identical sensors capable of responding to a particular gas or vapour. The present invention also relates to a method for detecting a gas or a vapour from the artificial olfactory system (100), comprising the step of exposing the gas or vapour to the plurality of sensors (121) to produce a plurality of output signals from the plurality of sensors (121); transferring the plurality of output signals to the data acquisition system (104); extracting median data from the plurality of output signals; applying a principal component analysis (PCA), neural network, and least square regression analysis on the median data from all of the plurality of clusters (120).